Political prisoners' memoirs in Zimbabwe: Narratives of self and nation - Alexander, J (Routledge, 2008)
Prison narratives are a key genre of African nationalist writing. They offer a unique window onto the relationships between the personal and political, the self and nation. This article focuses on the memoirs of three Zimbabwean political prisoners in order to explore claims to agency in prison, constructions of gender and race, and the complexities of individual passages within the collective narrative of nationalism. The memoirs are revealing of a formative period in Zimbabwean nationalism, and of the individuals and ideas that shaped independent Zimbabwe.